Clinicopathological manifestations of coexistent monoclonal immunoglobulin deposition disease and immunotactoid glomerulopathy - Wang, Yina; Yan, Yu; Dong, Bao; Zou, Wanzhong; Li, Xin; Shao, Chunying; Jiang, Lei; Wang, Mei; Zuo, Li (Frontiers in Medicine, 2022)
Combination of monoclonal immunoglobulin deposition disease (MIDD) and immunotactoid glomerulopathy (ITG) is a rare form of monoclonal immunoglobulin (MIg)-associated renal disease. We retrospectively reviewed the native kidney biopsy specimens at Peking University People’s Hospital from 2011 to 2020. Five patients were diagnosed as MIDD + ITG. Their clinical and pathological characteristics were studied. The typical clinical features were nephritic syndrome and renal dysfunction with prominent anemia, but hematuria was mild. Unlike single MIDD and single ITG, on light microscopy, segmentally distributed mesangial nodular sclerosis on the basis of mesangial matrix hyperplasia was the major lesion. Others including membranoproliferative glomerulonephritis (MPGN)-like lesion, glomerular basement membrane thickness, and mild to moderate mesangial and endothelial proliferations might presented at the same time and in the same glomeruli. On immunofluorescence, MIg, usually monoclonal light chains, deposited along glomerular basement membranes and tubular basement membranes, while the intact MIg or monoclonal heavy chain deposited in the mesangial regions. Corresponding to the depositions on immunofluorescence, punctate “powdery” deposits along glomerular basement membranes and tubular basement membranes under electronic microscopy indicated the presence of MIDD. Microtubular substructures (diameters of 20–50 nm) exhibiting hollow cores arranged in parallel arrays in mesangial regions indicated the presence of ITG. Patients treated with bortezomib-based regimen seemed to have better outcomes. In conclusion, MIDD + ITG is a rare combination form of MIg-associated renal disease. Accurate diagnosis requires the comprehensive pathological investigations.